Teaching Romanian as a Foreign Language between Integration and Exclusion: The Romanian Language as Cultural Capital and Power Relations in the University Environment - Ionescu, Bianca Raluca (Didactica Danubiensis, 2026)
This paper explores the teaching of Romanian as a foreign language within the broader sociological framework of integration and exclusion in the university environment. The study examines how the Romanian language serves as both a communication tool and a legitimate form of cultural capital that influences international students social positioning in Romanian universities, drawing on Pierre Bourdieu’s theories of cultural capital and symbolic power. The paper focuses on the asymmetrical relationship between teachers and international students, the function of linguistic norms, and the mechanisms of evaluation and assessment in order to highlight the power relations ingrained in the pedagogical process. Although learning Romanian makes it easier to participate in school and integrate socially, unequal access to linguistic and cultural resources can also lead to processes of marginalization and symbolic exclusion. The study highlights how institutional norms, expectations, and power structures are inextricably linked to language learning by taking a sociological stance. The results highlight the necessity of inclusive and reflective teaching methods that recognize cultural diversity and lessen the symbolic obstacles that foreign students must overcome. This paper has theoretical academic value, contributing to the understanding of Romanian language teaching as a social phenomenon by integrating the concepts of cultural capital and power relations within the university context. It is relevant to the sociology of education, intercultural studies, and foreign language didactics, offering a reflective perspective on the integration of international students. In the end, the analysis makes the case that teaching Romanian as a foreign language should be viewed as a social process that both facilitates integration and perpetuates current disparities in the academic community.